CircPlekha7 plays an anti-fibrotic role in intrauterine adhesions by modulating endometrial stromal cell proliferation and apoptosis - Wei XIE; Min HE; Yuhuan LIU; Xiaowu HUANG; Dongmei SONG; Yu XIAO (The Society for Reproduction and Development, 2020)
Circular RNA (circRNA) plays a key role in the development and progression of several diseases; however, its role in intrauterine adhesions (IUAs) is not well understood. This study aims to investigate the expression profiles and potential role of circRNA in IUA. RNA-sequencing was performed to screen for abnormally expressed circRNAs in TGF-β1-induced IUA endometrial stromal cell (ESC) model (IUA group) and an SMAD3 inhibitor, SIS3-treated IUA ESC model (SIS3 group). Gene Ontology enrichment and Kyoto Encyclopedia of Genes and Genomes pathway analyses were performed to uncover the key functions and pathways. Interaction networks were constructed and analyzed based on the competing endogenous RNA hypothesis of circRNA. CircRNAs were validated by Sanger sequencing and quantitative polymerase chain reaction (qPCR). Cell proliferation and apoptosis were measured using MTS and flow cytometry, respectively. The protein and mRNA expression levels of fibrosis-related proteins were measured using western blotting and reverse transcription-qPCR, respectively. A total of 66 circRNAs were differentially expressed between the IUA and SIS3 groups. CircPlekha7 was identified as one of the significantly upregulated circRNAs in the SIS3 group. Overexpression of circPlekha7 enhanced apoptosis, decreased the viability of ESCs, and suppressed the expression of α-SMA, collagen I, and SMAD3 in ESCs; whereas knockdown of circPlekha7 exhibited opposite results. Altogether, the results indicate that circPlekha7 plays an anti-fibrotic role in IUA and may serve as a promising prognostic biomarker for patients with IUA. Therefore, overexpression of circPlekha7 could be a potential treatment strategy for IUA.